The transformational festival as a subversive toolbox for a transformed tourism: lessons from Burning Man for a COVID-19 world. Issue 3 (26th May 2020) - Rowen, Ian
Abstract: Examining transformational festivals can offer conceptual resources for a transformation of tourism into a more responsible and sustainable practice. By thinking together two usually distinct scholarly treatments of "transformation"—those of transformational tourism and those of transformational festivals—the COVID-19 pandemic can itself also be treated as a spatiotemporal threshold for the transformation of the travel industry. This approach can also help deconstruct the mechanisms that sustain deleterious aspects of tourism's guest-host divide. As borders reopen and mobility and recreation recommences, the capacity of transformational festivals—both within and beyond their highly porous time-spaces– to transform their participants offer lessons for the blurring, if not the outright obliteration of the demarcation between guests and hosts. The creative and pro-social responses of members of one such transformational festival culture—Burning Man– to this and past crises are presented as examples for how values such as participation and civic responsibility may help people overcome shared conditions of hardship, and support more sustainable tourism practices in the post-COVID-19 world. Such subversive inter-subjective inversions may bring the recognition, in-itself, and production, for-itself, of a shared humanity of co-creators and participants in not just ephemeral, but accretive transformational social and environmental projects.